Comparison of Hatha Yoga and Elderly Exercise in Quality of Life in Elderly - Santoso, Rhevensa; Kesoema, Tanti Ajoe; Dewi, Novita Sari (Surabaya Physical Medicine and Rehabilitation Journal, 2025)
Background: Aging-related physical changes impact Quality of Life (Qol). Even though it is a popular form of exercise for the elderly, few of them are aware of the many advantages of Hatha Yoga. Aim: This study compares elderly exercise programs with Hatha Yoga in an effort to enhance quality of life in older adults. Material and methods: This was a randomized controlled trial consisting of 26 participants split into two groups: 13 people did Hatha Yoga and 13 people did senior exercise. For six weeks, both groups participated in three-week exercises, and the EQ-5D-5L was used to measure quality of life both before and after the intervention. Results: The elderly exercise group's delta post-test utility index score (0,15 ± 0,10) was lower than that of the Hatha Yoga group (0,46 ± 0,11); this difference was statistically significant (<0,001). The VAS score in the Hatha Yoga group (85,15 ± 7,38) was higher than that of the elderly exercise (74,15 ± 7,97) and the difference was significant (p=0.001). The difference in the score of Hatha Yoga (13,62 ± 5,47) compared to elderly exercise (2,46 ± 1,98) results in a significant p<0.001. Conclusions: Hatha Yoga improves better EQ-5D-5L than elderly exercises to improve the QoL of elders. Keywords: elderly, EQ-5D-5L, exercise, hatha yoga, quality of life